2019
DOI: 10.1111/jcmm.14460
|View full text |Cite
|
Sign up to set email alerts
|

Growth‐associated protein 43 promotes thyroid cancer cell lines progression via epithelial‐mesenchymal transition

Abstract: Thyroid cancer is maintaining at a high incidence level and its carcinogenesis is mainly affected by a complex gene interaction. By analysis of the next‐generation resequencing of paired papillary thyroid cancer (PTC) and adjacent thyroid tissues, we found that Growth Associated Protein 43 (GAP43), a phosphoprotein activated by protein kinase C, might be novel markers associated with PTC. However, its function in thyroid carcinoma has been poorly understood. We discovered that GAP43 was significantly overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Cancer and diabetes mellitus, one of the most common endocrine system disorders, have been shown to have pathogenic overlaps with PD, thus the involvement of the same proteins in PD and these two prevalent diseases ( Khwanraj et al, 2016 ; Sergi et al, 2019 ). Notably, the proteins which had the biggest fold change in differentiated hVM1 clone 32 cells, GAP43, DCLK1, and EEF1A2, are implicated in several cancers ( Patel et al, 2016 ; Giudici et al, 2019 ; Zheng et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cancer and diabetes mellitus, one of the most common endocrine system disorders, have been shown to have pathogenic overlaps with PD, thus the involvement of the same proteins in PD and these two prevalent diseases ( Khwanraj et al, 2016 ; Sergi et al, 2019 ). Notably, the proteins which had the biggest fold change in differentiated hVM1 clone 32 cells, GAP43, DCLK1, and EEF1A2, are implicated in several cancers ( Patel et al, 2016 ; Giudici et al, 2019 ; Zheng et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…AKT, as a key component in PI3K-AKT signaling, mediates PC progression (18)(19)(20). The relationship between UBE2C and EMT induction, which is also integral to metastatic tumor progression (18)(19)(20)(21)(22)(23)(24), was further analyzed, although no relationship between the two was identified. Further analyses revealed a strong association between Akt activation and the expression of UBE2C.…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with Italian, Icelandic, American, Dutch, Spanish, and Polish studies, which reported DIRC3 rs6759952 showed the strongest association with thyroid cancer in adults [ 12 , 23 ] GAP43 is a membrane phosphor protein that plays an integrative function in the brain and is expressed at high levels in the developing brain. GAP43 also promotes thyroid cancer tumorigenesis and tumor progression [ 24 ]. However, no study has yet demonstrated an association between GAP43 SNPs and thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%